Brown bear attacks on humans: a worldwide perspective - Bombieri, G.; Naves, J.; Penteriani, V.; Selva, N.; Fernández-Gil, A.; López-Bao, J.V.; Ambarli, H.; Bautista, C.; Bespalova, T.; Bobrov, V.; Bolshakov, V.; Bondarchuk, S.; et al.
Article number: 8573 2019